LEGAL ANALYSIS AND MODERN SIGNIFICANCE OF THE CANADIAN CONSTITUTION (Eureka Journal of Education & Learning Technologies, 2026)
This article provides a legal analysis of the Constitution of Canada, exploring its historical evolution and contemporary significance in a democratic framework. The study examines the transition from the British North America Act of 1867 to the full patriation of the Constitution in 1982. Key aspects such as the Canadian Charter of Rights and Freedoms, the division of powers between federal and provincial governments, and the unique constitutional amending formulas are discussed in detail.
Keywords: Constitution of Canada, federation, patriation, Charter of Rights and Freedoms, constitutional monarchy, parliamentary democracy, 7/50 formula.